2019
DOI: 10.1007/s10900-018-00612-7
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Perceived Stress and Hypertension Among Asian Americans: Does Social Support and Social Network Make a Difference?

Abstract: Background: Prior research suggests that stress plays role in the etiology and progression of hypertension. To lend a more accurate depiction of the underlying mechanisms between stress and hypertension, this study aims to assess the associations between perceived stress and hypertension across varying levels of social support and social network among Asian Americans. Methods: We conducted a cross-sectional study using data on 530 Chinese, Korean and Vietnamese Americans recruited from a liver cancer preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 54 publications
1
43
0
8
Order By: Relevance
“…et al, which indicate low social support is associated with coronary heart diseases [37]. Several studies also documented the role of social support in CVD incidence and mortality [38][39][40]. Both objective social isolation and the subjective perception of being isolated have been shown to be associated with a higher rate of CVD [41,42].…”
Section: Plos Onementioning
confidence: 99%
“…et al, which indicate low social support is associated with coronary heart diseases [37]. Several studies also documented the role of social support in CVD incidence and mortality [38][39][40]. Both objective social isolation and the subjective perception of being isolated have been shown to be associated with a higher rate of CVD [41,42].…”
Section: Plos Onementioning
confidence: 99%
“…9 Similar to the finding of this study, previous studies have also observed a higher number of female patients. 9,21 The majority of the participants in this study were either overweight or obese (79.1%). This may be because being overweight is a risk factor for hypertension.…”
Section: Discussionmentioning
confidence: 86%
“…19,20 Psychological stress may be influenced by both internal and external factors 9 , and there are many factors influencing psychological stress in hypertension; such as: illness perceptions, religiosity, perceived social support, physical activity, health literacy, hope, resilience, and coping behaviors. 10,21,22 As in the Common-Sense Model of Self-Regulation, psychological distress was one of the distinct categories of illness outcomes, and has been predicted by illness perceptions and coping strategies. 23 Previous studies reported illness perception as a predictor of psychological stress (R 2 =0.48, p-value<0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proven the role of chronic stress in the formation and progression of arterial hypertension in particular and CVDs in general, directly potentiating systemic inflammation, as well as indirectly influencing behavioral changes. In a study by Lu X, et al (2019) shows that the association of stress with arterial hypertension changed by gender and ethnicity [14]. Asian-American men with high levels of stress were significantly more likely to develop arterial hypertension than men with low stress.…”
Section: Resultsmentioning
confidence: 99%